Improving Children’s Moral Character through the Cultural Practice of “TABEA” in Guu Village, Batuatas Subdistrict, South Buton Regency - Masriyanto, Masriyanto; Rahim, Abdul; Ridwan, Muhamad (Edumaspul: Jurnal Pendidikan, 2026)
This study examines how tabea a living local cultural practice in the daily life of Guu Village, Batuatas District, South Buton Regency contributes to the formation and improvement of children’s moral character. Tabea functions as an embodied expression of respect, politeness, and social ethics that is continuously transmitted across generations through everyday interaction. The research employed a descriptive qualitative design. Data were collected through direct field observation, in-depth interviews with parents, teachers, community leaders, and children, as well as documentation of community practices and school-related activities. The findings indicate that the consistent enactment of tabea within the family, school, and broader community significantly supports children’s character development, particularly in cultivating courteous speech and behavior, respect for elders, self control in social interaction, and a growing sense of social responsibility. Moreover, tabea strengthens children’s awareness of social norms and reinforces positive role modeling through habituation and community supervision. These results suggest that tabea is not merely a symbolic tradition, but a practical mechanism of character education embedded in local wisdom. Therefore, preserving and revitalizing tabea should be pursued through collaborative strategies involving families, schools, and village institutions, and integrated sustainably into educational patterns to strengthen the moral foundation of the younger generation.